Post-implementation review of the net metering policy in Namibia and design of distributed generation hosting capacity algorithm - Sam, Angula Markus (Department of Electrical Engineering, 2021)
Global campaigns against fossil fuels to reduce the emission of greenhouse gases and combat climate change has compelled the electricity supply industry (ESI) around the globe to explore environmentally friendly sources of electricity. The concept of distributed generation (DG) has gained momentum and is emerging as a promising source of clean energy, with immense potential to maximize the shares of renewable energy in the global energy mix. Like the rest of the world, Namibia is witnessing an unprecedented growth of DG courtesy of governmental efforts to ensure a speedy transition to low-carbon generation technologies. In 2016, the Namibia government developed the net metering (NM) policy known as the Net Metering Rules (NMR) as a consumer-focused approach to achieve the low-carbon objective. To date, there has been no rigorous post-implementation review of the NMR to assess its effectiveness, despite rising concerns from distribution network operators (DNOs) about whether the NMR is suited for long-term application in the fast-growing market of prosumers. This study conducts a broad appraisal of the status quo on DG integration into distribution networks in Namibia and an in-depth assessment of the technical and financial impacts of the NMR using the Erongo Regional Electricity Distributor (Erongo RED) as a case study. The findings indicate that most prosumers export over 60% of generated energy to distribution networks and achieve significant financial savings by offsetting on-site demand with their generation in real-time, as well as, by offsetting a portion of their electricity bills through NM compensations for grid exports. NM compensations at the avoided cost makes grid exports in Namibia a cheaper alternative source of energy to DNOs as compared to the national utility, which charges other energy service charges i.e. reliability charge, transmission losses charge etc. on top of the avoided cost. Additional findings indicate that prosumers are subjecting DNOs to revenue losses because of reduced volumetric energy sales caused by the reduction of prosumers' on-site energy requirements from the grid. With the deployment of DG growing rapidly in Namibia, increasing grid exports and associated technical constraints are envisaged in distribution networks. This dissertation recommends adaptations to existing regulatory policies to mitigate envisaged financial and technical risks associated with DGs. These adaptions include a DG hosting capacity (HC) assessment methodology for consumer-side photovoltaic (PV) DG in existing distribution network where a high and uniform uptake of DG is anticipated. The methodology captures time dependency correlations between load and generation profiles, which increase the accuracy of HC results. The uniqueness of the methodology is the concept of calculating monthly HC, which aids the optimal integration of DG into distribution networks to meet consumers' daily energy requirements throughout the year without comprising the network's quality of supply. The methodology was tested on a residential and business distribution network. Results confirm that HC in distribution networks varies monthly. However, the practical implementation of monthly HC require upgrades to existing inverter technology, which currently contains a single export limit functionality. This opens the possibility to drive innovation in the inverter technology, to develop a date-based multiple export limit functionality. The results also demonstrated the importance of considering phase unbalance when conducting HC studies for residential distribution networks. Applications and limitations of the methodology were discussed.